CHANGE OF BIOCHEMICAL INDICATORS IN ORAL LIQUID AFTER DENTAL IMPLANTATION FOR TREATMENT OF PARTIAL EDENTIA - I. A. SEVOSTYANOV; I. M. BYKOV; T. V. GAYVORONSKAYA (Кубанский научный медицинский вестник)
Aim. To study the electrolytic composition and state of the prooxidant-antioxidant system of the oral fluid after dental implantation.Materials and methods. 25 patients suffering from the partial edentia (the 2nd group of 13 patients with 1-3 teeth missing and the 3rd group of 12 patients with 4-6 teeth missing) and 20 healthy volunteers (the 1st group) took part in the study. The non-stimulated oral fluid was collected using the Ti Grade 4 implants during their first visit and 6 months after the dental implantation. The electrolytic composition, content of products of oxidative biomolecular modification and the activity of antioxidative protection enzymes of the oral fluid have been studied.Results. It has been demonstrated that in partial edentia the level of sodium ions in the oral fluid increased 3-5 times while the level of iron ions increased 5-11 times. At the resampling of the oral fluid after the performed dental implantation the decrease in iron content down to the control indices has been determined in both groups of patients. In 6 months after restoration of denture by means of the dental implants the significant changes in the oxidative metabolism of the patients’ oral fluid have been revealed. So the content of products of oxidative biomolecular modification in the oral fluid of the patients suffering from partial edentia with 1-3 teeth missing decreased to the indices similar to those of the control group; in patients with 4-6 teeth missing the level decreased by 26% in comparison with the indices of the same group before treatment. The catalase activity of oral fluid in the second group decreased by 52% after treatment which can be associated with the production increase in hydrogen peroxide and the accompanying decrease in necessity of enzyme functioning. After the dental implantation against the background of the decreased indices before treatment the activity of glutathione peroxidase increased in the 2nd group 2,1 times and in the 3rd group 1,7 times reflecting the partial restoration of the protective potential of the oral fluid.Conclusion. The tendency to the normalization of functioning of the prooxidant-antioxidant system and the electrolytic exchange in the oral fluid of patients suffering from the partial edentia after the dental implantation has been demonstrated.